Key Success Factors Islamic Human Resources in North Sumatera Islamic Banking With Analytical Network Process (ANP) - Lubis, Rukiah; Matondang, Zulaika; Cahyani, Utari Evy (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The development of Islamic banking in Indonesia has experienced very rapid growth. On the other hand, the availability of Islamic human resources is not in accordance with the standards expected by Islamic banking. This is indicated by a large number of human resources graduates from public universities compared to graduates of Islamic banking or Islamic economics. The purpose of this study is to analyze the factors that determine the success of Islamic HR in Islamic banking in North Sumatera. Data analysis was carried out using the ANP approach. The results of this study indicate that problems related to the determinants of the success of Islamic HR in North Sumatera internally are the most important internal performance appraisal and self-quality improvement in the form of knowledge, skills, and abilities (KSA). There are internal and external factors to improve Islamic human resources at sharia banking. From the internal factors, Sharia banking needs to develop a performance appraisal system from the perspective of Sharia compliance and financial risk. The Islamic bank employee recruitment system must also comply with sharia principles. In addition, it needs training and education by instilling sharia concepts. Finally, improving the quality of human resources through developing soft skills, increasing work motivation, sharia work ethic with the itqan. External factors are from universities in the form of curriculum and regulations from the government. The solution is to create a standard system for developing Islamic human resources and compile a curriculum that is in accordance with KSA. Keywords: anp, islamic bank, islamic human resources, key success factors